El redimensionamiento del derecho internacional del trabajo - Canessa Montejo, Miguel Francisco (Pontificia Universidad Católica del Perú, 2012)
The resizing of International Labor LawThe transformations brought about by the globalization of the labour world render insufficient the national efforts to face a cross-boundaries phenomenon. Similarly, the International Labour Organization efforts are praiseworthy but incomplete because its Members are reluctant to new international commitments. In this situation, labour human rights are in the best position to face the challenges of globalization.